FAKTOR – FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Apit Susanti; Sekar Mayangsari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
The purpose of this research is to examine the effect of insider ownership, institutional ownership, dividend policy, asset structure, profitability, firm growth, and business risk to debt policy. This research is developed based on the previous research carried out by Murni and Andriana (2007). Data were taken from all companies are listed at Indonesian Stock Exchange for three years (2009-2011) except financial, insurance, and other financial industries. Sample selection were based on purposive sampling. Only 45 companies meet the criteria and taken as sample. For this study SPSS 11.5 program is used to find out the effect from all independent variable above to dependent variable. The statistical used in this research was multiple regression. The research showed that institutional ownership, asset structure, profitability, and firm growth had effect to debt policy but insider ownership, dividend policy, and business risk had no effect to debt policy.